Effects of selected peripheral rewarming methods on vital signs among patients post coronary artery bypass graft (CABG) - Avellona, Mylene K. (1998)
This research proposed to compare the effects of cellophane, overhead heat lamp and blanketroll as peripheral rewarming methods on the vital signs of adult patients who underwent coronary artery bypass graft. It also attempted to find out the confounding effects of the physical and surgical factors on the vital signs during rewarming. The factors that influence the selection of peripheral rewarming methods as perceived acceptability and ease of administration by nurse care provider were identified.Specifically, the study answered the following questions:1. Is there a significant difference among the three rewarming methods on the mean gain score of: a.) body temperature b.) blood pressure c.) heart rate d.) heart rhythm at a.) 30 mins. post-operatively b.) 60 mins. post-operatively c.) 120 mins. post-operatively d.) 240 mins. post-operatively?2) Is there significant relationship among physical factors such as: a.) age b.) sex c.) BSA d.) status of hydration; and the vital signs such as: a.) body temperature b.) blood pressure c.) heart rate d.) heart rhythm at a.) 5 mins. post-operatively d.) 30 mins. post-operatively c.) 60 mins. post-operatively d.) 120 mins. post-operatively e.) 240 mins. post-operatively?3) Is there a significant relationship among surgical factors such as: a.) surgical procedures done b.) total bypass time c.) degree of hypothermia intraoperatively d.) length of surgery e.) temperature at end of surgery and the vital signs at a.) 5 mins. post-operatively b.) 30 mins. post-operatively c.) 60 mins. post-operatively d.) 120 mins. post-operatively e.) 240 mins. post-operatively?4) What factors influence the selection of peripheral rewarming methods?a.) Perceived acceptability of the nurse care providerb.) Perceived ease of administration by the nurse care providA total of 85 subjects were included in the study, 5 subjects were dropped out due to insertion of Intraaortic Balloon Pump (IABP) post-operatively. Subjects were randomly assigned to those treatment groups. Experimental group 1 was treated with cellophane + blanketroll, experimental group 2 were treated with overhead heat lamp + blanketroll, and a control group treated with blanketroll alone. The three groups were compared as to their effect on vital signs; temperature, blood pressure, heart rate, and heart rhythm during different time intervals post-operatively. The treatment methods were initiated once patient was noted to be hypothermic, and were stopped once the patient's temperature normalized. Vital signs of subjects were taken and recorded 5 mins, 30 mins, 60 mins, and 120 mins, and 240 mins. post-operatively?Other pertinent data as total bypass time, surgical procedure done, length of surgery, temperature at end of surgery, degree of hypothermia intraoperatively were taken from the operative record.The findings of the study showed the following results:1. The use of blanketroll significantly differ in temperature compared with the use of cellophane + blanketroll at 30 mins. and 60 mins. post-operatively. The higher mean indicated that blanketroll remained to be the most effective method to rewarm.2. The use of overhead heat lamp + blanketroll did not differ significantly with the two other methods, however, a mean temperature gain of 0.44?C 60 mins. post-operatively indicated some degree of heat gain.3. Hydration was significantly related to temperature at 5 mins. and 30 mins. post-operatively. Poorly hydrated patients had greater degree of temperature afterdrop and slower to rewarm than those who were well hydrated.
4. Several surgical factors related to vital signs were:4.1. Surgical procedure done related to blood pressure at 30 mins., 60 mins., 120 mins., and 240 mins. post-operatively. The more coronary vessels involved during surgery, the lower and more unstable the blood pressure.4.2. Total bypass time was significantly related to blood pressure 30 mins. and 240 mins. post-operatively. The longer the bypass time, the lower and more unstable the blood pressure at 30 mins. and 240 mins. post-operatively.4.3. Temperature at end of surgery and length of surgery were significantly related to blood pressure 30 mins. and 120 mins. respectively, post-operatively. These mean that the higher the temperature at end of surgery, the more stable the blood pressure while longer surgical time caused a more unstable blood pressure.5. Total bypass time was another predictor of vital signs specifically heart rate at 5 mins. and 240 mins. post-operatively. The longer the bypass time, the more tachycardic (increased heart rate) the patient at 5 mins. and 240 mins. post-operatively.6. Significant predictors of heart rhythm included degree of hypothermia intraoperatively. A negative relationship existed among degree of hypothermia intraoperatively and heart rhythm at 30 mins. post-operatively. This means that the more severe the hypothermia intraoperatively, the lesser the cardiac arrhythmia observed. This could be attributed to the thorough rewarming done to patients who experienced severe hypothermia intraoperatively. As the patient's temperature normalized 240 mins. post-operatively, rewarming is stopped and the relationship among the two variables become positive. There was an increased incidence of cardiac arrhythmia observed to patients with severe hypothermia intraoperatively.7. Blanketroll was perceived as the most acceptable and easy to administer method of rewarming by the nurse care providers. The most common reason was it restored temperature to normal faster than the other methods.8. Comparing heatlamp and cellophane, nurses preferred heatlamp over cellophane. Heatlamp had a more tangible and visible source of heat.Nursing Practice. Limited to those who have undergone CABG.1. The blanketroll be used to rewarm adult hypothermic post-operative cardiac surgery patients especially during the first 30 mins. to one hour after surgery.2. That the standards for monitoring pre and post CABG should include:2.1. Status of hydration which include parameters as complete blood count, hemoglobin, hematocrit, serum Na, blood osmolality, and physical examination on skin turgor and tautness.2.2. Temperature and blood pressure monitoring every 30 mins. for the first two hours and hourly for the next twelve hours post-operatively.3. That total bypass time, total surgical time, surgical procedure done, temperature at end of surgery, and the degree of hypothermia intraoperatively be a vital part of recovery room and surgical intensive care unit (SICU) nurse's flowsheet and be a vital part of the endorsement.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Patient monitoring; Vital signs; Peripheral rewarming methods